2009
DOI: 10.1038/ijo.2009.131
|View full text |Cite
|
Sign up to set email alerts
|

Fetal macrosomia and adolescence obesity: results from a longitudinal cohort study

Abstract: Objective: To assess the association between fetal macrosomia and adolescent obesity. Design: Longitudinal cohort study of the association between macrosomia and adolescent obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 31 publications
(35 reference statements)
3
43
0
4
Order By: Relevance
“…It is considered that low birth weight infants were susceptible to obesity at the age of 5 years [24]. On the other hand, studies found that macrosomia was also an independent risk factor for childhood and adolescent obesity [30]. Our study confirmed this finding: birth weight of 4,000 g or greater (i.e., macrosomia) was a risk factor of childhood obesity.…”
Section: Discussionsupporting
confidence: 88%
“…It is considered that low birth weight infants were susceptible to obesity at the age of 5 years [24]. On the other hand, studies found that macrosomia was also an independent risk factor for childhood and adolescent obesity [30]. Our study confirmed this finding: birth weight of 4,000 g or greater (i.e., macrosomia) was a risk factor of childhood obesity.…”
Section: Discussionsupporting
confidence: 88%
“…Because children with low or high birth weight may have a different obesity risk later in life and because size at birth may have been influenced by intrauterine exposures, we conducted sensitivity analyses restricting the sample to children in the normal range of weight at birth (2,500–4,000 g; n = 318) (Oken and Gillman 2003; Wang et al 2009; Wojtyniak et al 2010). As a sensitivity analysis we also assessed the effect of excluding those assumed to be diet misreporters.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] In addition, there are many factors that influence infants' weight after they are born, such as gender, the duration of breastfeeding, and the quality and quantity of formula feeding. [25][26][27][28][29] In the first 3 months of their lives, there are no significant differences in weight among the infants with respect to gender and temperament group. We have two explanations for this: Firstly, from the 42nd day of birth to 3 months, the weight of an infant is highly influenced by his or her birth weight.…”
Section: Physical Developmentmentioning
confidence: 95%